Understanding the molecular pharmacology of vascular calcium-activated chloride channels - Dinsdale, R (2021)
Calcium-activated chloride channels (CaCCs) are a class of ion channel involved in a multitude of cellular functions. The role of CaCCs is especially well recognised in vascular smooth muscle cells (VSMCs), where CaCCs are activated by agonist-induced Ca2+ release and their opening triggers depolarisation leading to vasoconstriction. CaCCs have been proposed as new potential therapeutic targets for diseases of altered blood vessel tone including systemic and pulmonary hypertension, as well hypotension and shock. Selective and potent CaCC modulators, however, are currently missing. Our lab has previously demonstrated that anthracene-9-carboxylic acid (A9C) has a biphasic effect on TMEM16A currents, producing both activation and inhibition depending on the concentration range and membrane potential. Defining the mode of action of this test compound can therefore help the design of both synthetic inhibitors and activations. Patch-clamp electrophysiology of cloned and native ion channels was used in conjunction with single point mutagenesis and wire myography to gain insights on the molecular pharmacology of TMEM16A-CaCCs. The main findings of this thesis are: 1. The selectivity of two of the most potent modulators of TMEM16A currently available 2-(4′-chloro-2′-methylphenoxy)-N-[(2′′-methoxyphenyl)methylideneamino]-acetamide (Ani9) and N-((4′-methoxy)-2′-naphthyl)-5-nitroanthranilic acid (MONNA) was studied on isolated mouse VSMCs and isolated aortic rings. Ani9 potently blocked cloned and native TMEM16A channels, without interfering with other conductance’s in mouse aortic SMCs. MONNA was found to inhibit cloned and native TMEM16A channels. However, MONNA also activated BKCa channels and inhibited CaV channels, significantly affecting the tone of aortic rings through a combined action of multiple conductance’s. 2. The mode of action of A9C on the TMEM16A channel was elucidated. TMEM16A channels with the activation gate constitutively open were used to dissect the mechanism of A9C inhibition and activation. These channels were found to be entirely insensitive to A9C in the absence of intracellular Ca2+. However, when intracellular Ca2+ was presence, the mutant channels regained their sensitivity to extracellular A9C. Thus, intracellular Ca2+ is mandatory for the channel response for extracellular A9C. The underlying mechanism is an unanticipated conformational change in the outer pore, revealing a novel aspect of Ca2+-gating in the TMEM16A channel, and its implication for channel pharmacology. 3. A fluorescence-based screening cellular system was developed to enable a higher through-put evaluation of possible compounds that modulate TMEM16A function. This method was tested using known modulators of the TMEM16A channel. This cell system may help future drug screening exercises. To conclude, the research in this thesis has led to the determination of the binding site of A9C on the TMEM16A channel and revealed that the binding site become accessible to A9C only when intracellular Ca2+ is present; this indicates a possible site for therapeutic drug targets that can become accessible during stimulation of the cell by factors that trigger Ca2+ release (such as stimulation of VSMCs by vasoactive agonists). The pharmacology of TMEM16A was also systematically studied and the selectivity of two of the most commonly used tool compounds defined, which enables a more in-depth interpretation of published results involving these modulators. Collectively, these data advance our understanding of the pharmacology of the TMEM16A channel. The definition of a ligand binding site may form the basis for the rational design of small molecules acting at this site.